Polarization-based super-resolution imaging of surface-enhanced Raman scattering nanoparticles with orientational information - Wang, M. Y.; M. Chen; Zhanghao, K.; X. Zhang; Jing, Z. L.; Gao, J. T.; Zhang, M. Q.; Jin, D. Y.; Dai, Z. F.; Xi, P.; QH Dai (Nanoscale, 2018)
Raman scattering provides key information of the biological environment through light-molecule interaction; yet, it is generally very weak to detect. Surface-enhanced Raman scattering (SERS) can boost the Raman signal by several orders-of-magnitude, and thus is highly attractive for biochemical sensing. However, conventional super-resolution imaging of SERS is challenging as the Raman signal is generated from the virtual state which cannot be easily modulated as fluorescence. Here, we demonstrate super-resolution microscopy with a surface-enhanced Raman scattering (SERS) signal, with a resolution of approximately 50 nm. By modulating the polarization angle of the excitation laser, the SERS nanorods display a dramatic anisotropy effect, allowing nanoscale orientation determination of multiple dipoles with dense concentration. Furthermore, a well-established defocused analysis was performed to reconfirm the orientation accuracy of super-resolved SERS nanorods. Sub-diffraction resolution was achieved in the imaging of SERS nanorod labeled vesicles in fixed macrophages. Finally, we demonstrate dynamic SERS nanorod tracking in living macrophages, which provides not only the particle trajectory with high spatial resolution but also the rotational changes at the nanometer scale. This pioneering study paves a new way for subcellular super-resolution imaging with the SERS effect, shedding light on wider biological applications.
Keywords: resolution